MEMBANGUN DEMOKRASI DI ATAS KEPENTINGAN RAKYAT (ILUSI KEPENTINGAN RAKYAT) - Bibianus Hengky Widhi Antoro (Justitia et Pax, 2016)
ABSTRACTPolitical party plays an important role in the democratic process of a country due to its role as a political infrastructure in an attempt to print a cadre of state leaders in the executive and legislative branches, which is a political suprastructure. Te correlationof both branches arevery important in the realization of the rule of law, which is based on democratic principles. In order to strengthen democracy and the implementation of an eﬀective party system, strengthening the institutions and improving the function and the role of political party are needed.Tus, public funds (public fnancing) is nedeed by the political party to support operational activities of political education and political party secretariat. In relation with that issue, the fnancial disclosure at the level of internal party democracy is nedeed. Tis paper analyzes the fnancial support of political parties, in particular on the party funding arrangements system sourced from public funds, as referred to in the regulations governing the fnancial aid of the party with regard to the principles of good fnancial management and international standards that are built on people’s interests.Keywords : political party, democracy, political party fnance.INTISARIPartai Politik memegang peranan penting dalam proses demokrasi suatu negara. Mengingat perannya sebagai infrastruktur politik dalam upaya mencetak kaderkader pemimpin negara di eksekutif maupun legislatif yang merupakan suatu suprastruktur politik. Korelasi keduanya sangatlah penting di dalam perwujudan prinsip negara hukum yang didasarkan pada prinsip-prinsip demokrasi. Guna penguatan pelaksanaan demokrasi dan sistem kepartaian yang efektif diperlukan penguatan kelembagaan serta peningkatan fungsi dan peran Partai Politik. Sehingga dengan demikian diperlukan adanya pemberian bantuan keuangan partai yang bersumber dari dana publik (public fnancing) yang digunakan sebagai penunjangkegiatan pendidikan politik dan operasional sekretariat partai politik. Berkaitan dengan hal tersebut, perlu adanya demokrasi pada tataran internal partai untuk mewujudkan keterbukaan keuangan partai. Tulisan ini menganalisis tentang bantuan keuangan partai politik, secara spesifk pada sistem pengaturan pendanaan partai yang bersumber dari dana publik sebagaimana dimaksud dalam regulasi yang mengatur tentang bantuan keuangan partai dengan memperhatikan prinsip-prinsip pengelolaan keuangan yang baik dan standar internasional yang dibangun di atas kepentingan rakyat.Kata Kunci : Partai Politik, Demokrasi, bantuan keuangan partai.